Analisa Kelayakan Pasar Dan Lingkungan Pada Pengembangan Wisata Bahari Pelabuhan Muncar Banyuwangi - Estu Handayani (STIE Mandala Jember, 2020)
The current condition of the Muncar fish port is different from the condition 10 years ago, where around 2008 the port was famous for its biggest fish catch, namely for lemuru, tonggkol, and kite. At present the number of fish catches has decreased dramatically. This condition affects the economy of fishermen and the community around the port. With this condition, research was carried out on the analysis of market and environmental feasibility in the development of the Muncar fish port in Banyuwangi. The aim is to determine the feasibility of developing marine tourism in the Banyuwangi harbor in terms of market and marketing aspects as well as environmental aspects. The research method uses qualitative and quantitative analysis by analyzing market and marketing aspects as well as environmental aspects and conduct regression test analysis. The results obtained that the development of marine tourism in the port of Muncar is feasible. It is stated from the variable Promotion, Place, Price, and Product significantly influence the feasibility of the port and provide a positive influence on the development of marine tourism in the port of Muncar.